Phytophagous insects associated with avocado orchards (Persea americana Mill.) in the Colombian Caribbean - López-Galé, Yeison; Carrascal-Pérez, Francisco; Pulgarín Díaz, John Alexander; Burbano-Figueroa, Oscar; Arcila Cardona, Ángela (Revista Colombiana de Entomología, 2022)
Field studies were carried out in the three main productive nuclei: Montes de María (MM), Sierra Nevada de Santa Marta (SNSM) and Serranía del Perijá (SP), in order to determine the richness and composition of phytophagous insects associated with avocado plantations for the Colombian Caribbean region. The field studies were carried out in 78 farms, covering 26 sampling municipalities. For the capture of phytophagous insects, the manual capture method was used at the plant level, and white light traps and Ecoiapar-type attractive traps were installed at the plot level. With the data obtained, species accumulation curves, Multi Response Permutation Procedure analysis MRPP to determine differences in species composition and analysis of indicator species by productive nucleus were constructed. 42 species of phytophagous insects were identified, grouped in seven orders and 12 families. The most frequent taxonomic groups were termites (Blattodea: Isoptera), scale insects (Hemiptera: Coccomorpha), and branch borers (Coleoptera: Curculionidae). Between 63.4 % and 84.2 % of the expected species richness per productive nucleus was recorded according to the Chao-2 and Jacknife-1 estimators. The highest species richness was obtained in SP (30 species), followed by MM (26 species) and SNSM (16 species). The MRPP analysis detected significant differences in the composition of species between productive nuclei (p ≤ 0.05). The species Nasutitermes sp. for MM, Xylosandrus morigerus for SNSM and Atta sp. for SP they obtained indicator values that differed from those expected at random.